Determination of Eye Torsion by Videooculography Including Cornea Optics - Paliulis, E.; Daunys, G. (Elektronika ir Elektrotechnika, 2006)
Influence of optical characteristics of cornea on formation of image of iris and its signature is evaluated. A mathematical model of optical characteristics of cornea is created for this purpose. The nature of changes in geometric parameters of pupil, iris and its signature images, when the rotation of eye is performed, is analyzed. We concluded that optical characteristics of cornea influence iris and its signature images and those distortions should be considered when calculating torsion by the method of correlation of signature of iris. Original videooculography method to register torsional movements of human is created. It evaluates the influence of optical characteristics of cornea on the image of iris. This model reduces standard deviation of points on Listing planes on average by approximately 14% in comparison with previously used methods. Thus, it is significant to consider the influence of optical characteristics of cornea on image of iris when calculating torsional eye movements by the method of correlation of signature of iris. Ill. 8, bibl. 7 (in English; summaries in English, Russian and Lithuanian).